Faktor-Faktor yang Mempengaruhi Produksi Usahatani Kacang Tanah (Arachis Hypogaea L) di Kelurahan Attangsalo Kecamatan Ma’rang Kabupaten Pangkep - Yulianti Rahman; Abd. Asis Pata; Azisah Azisah (Universitas Muslim Maros, 2022)
This study is aimed at identifying factors that affect the production of corporate peanuts in Attangsalo District Ma’rang The District Of Pangkep. The method of analysis that defines a relationship of one loose variable (Y) with two free variable (X1, X2, Xn). Analytical tools used ias a factor analysis with version 25 of IBM SPSS 25. Studies have shown that factors affecting the production of kernels in either in Attangsalo District Ma’rang The District Of Pangkep are the land area, the amount of seeds while the amount of fertilizer does not affect the production of peanuts.